A vaccine against malaria: five minutes with . . . Richard Bucala. (8th March 2021) - Mahase, Elisabeth
Abstract : The Yale professor explains how his team's malaria vaccine candidate—which uses similar technology to the RNA covid-19 vaccines—came to be and how he is working with the Oxford Vaccine Group to test it